Quasi-fiscal operations of central banks in transition economies - Malgorzata Markiewicz (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
This paper reviews issues associated with quasi-fiscal operations (QFO) of central banks in a sample of countries in Central and Eastern Europe and the former Soviet Union.The concern is the problem of transparency in fiscal and monetary accounts when the central bank undertakes quasi-fiscal operations and the government falls short of providing full coverage of fiscal operations.QFO can also jeopardize monetary policy designed to maintain price stability.A simple framework is developed to estimate the extent of QFO.In some cases, the magnitude of QFO is significant in indicating underestimation of fiscal deficit figures.We claim that the lack of transparency in fiscal accounts of transition countries warrants serious concern.
URN:NBN:fi:bof-201408072160
Keywords: 330; Quasi-fiscal operations; transition economy and